LOW MOLECULAR WEIGHT HEPARIN AT HIGH DOSE IMPACTS ON OUTCOME OF COVID-19 HOSPITALIZED PATIENTS, WHILE STANDARD DOSE DOESN'T. (April 2021) - Bonetti, Silvia; Boari, Gianluca E.M.; Chiarini, Giulia; Faustini, Cristina; Bianco, Gianluca; Braglia-Orlandini, Federico; Malerba, Paolo; Rizzoni, Damiano
Abstract : Objective: COVID-19 is a new disease caused by pandemic SARS-CoV-2, that involves multiple organs and can cause a potentially fatal respiratory distress syndrome. Accumulating evidence point out that an "endothelitis" due to a cytokines storm causes intravascular thrombosis, especially in the lungs, and is related to the poor outcome. We tested possible relationships between anticoagulant treatment and/or administration of low molecular weight heparin (LMWH) at different doses and outcome in a population of 258 COVID-19 patients admitted from February 28th to April 30th, 2020 to General Medicine ward of the Hospital of Montichiari (Brixia, Italy). Design and method: A group of 258 consecutive patients (174 males and 84 females, mean age 71 years +/- 14) was included in the present study. In 168 patients, high-flow oxygen was required (Venturi mask), 6 patients needed orotracheal intubation and 20 were given continuous positive pressure oxygen therapy (CPAP). Patient were treated (unless a pulmonary embolism was detected) with different doses of prophylactic LMWH, according to emerging evidence during pandemic period. As of June 10th, 65 deaths had been observed. Survival curves were calculated according to Kaplan-Meier method. Comparison between groups was performed with Breslow and Mantel-Cox test. Results: LMWH at standard dose (4000 IU once daily) didn't reduce mortality compared to no treatment (p = ns), while LMWH at a higher dose than usual prophylactic dose (enoxaparin 6000 IU once daily or 4000 IU bid) was associated with better outcome (p < 0.001 vs untreated and treated with standard dose). Significance was confirmed adding patients treated with oral anti-coagulant (OAC)for any reason. None of the patients treated with LMWH at higher doses or OAC died. Figure. No caption available. Conclusions: The administration of subcutaneous LMWH at a higher dose than indicated for deep vein thrombosis prophylaxis is associated with a better outcome in patients with SARS-CoV-2 pneumonia, confirming some emerging evidence.